THE ROLE OF RATIONALETM APPLICATION ON STUDENTS’ CRITICAL THINKING SKILL IN ARGUMENTATIVE WRITING - Nova AlfiLaili Rahmah; Ahmad Munir; Syafi’ul Anam (Jurnal Education and Development, 2019)
This paper aims to evaluate an innovative way to teach argumentative writing by using an electronic learning. This paper will focus on writing skill because through writing the learner can express their idea in written form. However, there is a little guidance to encourage critical thinking skills in learning process, it makes students get difficulty to express and generate their ideas in writing, as a result they get stuck in the process of writing without being critical thinker. Because of this reason, the researcher promotes rational application as e-learning media to help the students learn concepts, understand argument structure, and develop reasoning skills. This paper used descriptive qualitative method to describe how the teacher implement rationale application and how the students’ critical thinking in their argumentative writing task. The result showed that rationale application provides students not only with greater motivation to write and to engage their creativity in writing argumentative text, but it also leads them to think critically of evaluating something.